2020
DOI: 10.1002/nau.24387
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of Vibegron in treating overactive bladder: A systematic review and pooled analysis of randomized controlled trials

Abstract: Objective Vibegron is a new kind of β3‐adrenergic receptor agonist. We performed a systematic review and pooled analysis to assess the efficacy, safety, and tolerability of Vibegron for treating overactive bladder (OAB). Methods MEDLINE, the Cochrane Controlled Trial Register and EMBASE were used to pick out randomized controlled trials (RCTs) of Vibegron in treating OAB. The reference lists of the retrieved articles were also studied. We used RevMan version 5.3.0. to analyze the data. Results Three high‐quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Although vibegron is associated with significant improvements versus placebo in micturition, UUI and maximum voided volume in patients with OAB symptoms with or without incontinence at baseline, there are currently no data in patients with OAB who have MUI. 20,21 As noted previously, incontinence is a particularly bothersome OAB symptom, associated with significant impairment in QOL. 8 In both the UUI and MUI populations, treatment with mirabegron 50 mg resulted in a higher frequency of responders in terms of incontinence normalization rates.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Although vibegron is associated with significant improvements versus placebo in micturition, UUI and maximum voided volume in patients with OAB symptoms with or without incontinence at baseline, there are currently no data in patients with OAB who have MUI. 20,21 As noted previously, incontinence is a particularly bothersome OAB symptom, associated with significant impairment in QOL. 8 In both the UUI and MUI populations, treatment with mirabegron 50 mg resulted in a higher frequency of responders in terms of incontinence normalization rates.…”
Section: Discussionmentioning
confidence: 79%
“…Vibegron, approved in Japan in 2018, is another selective β 3 ‐adrenergic receptor agonist. Although vibegron is associated with significant improvements versus placebo in micturition, UUI and maximum voided volume in patients with OAB symptoms with or without incontinence at baseline, there are currently no data in patients with OAB who have MUI 20,21 …”
Section: Discussionmentioning
confidence: 99%
“…This analysis demonstrated improvement in incontinence episodes ( p < 0.001), voided volume ( p = 0.005), and nocturia episodes ( p = 0.03) [ 38 ]. A systematic review on the efficacy of vibegron (β3-adrenoceptor agonist) included 3 RCTs and demonstrated improved urinary frequency, urgency and UUI episodes ( p < 0.0001) [ 37 ].…”
Section: Treatmentsmentioning
confidence: 99%
“…Recently approved, vibegron is a novel beta-3 agonist that has also shown efficacy in placebo-controlled studies including reduction of micturition episodes and urge incontinence episodes [48,49]. Furthermore, recent RCT data showed no difference in the rates of hypertension between patients on vibegron versus placebo [50].…”
Section: Beta-3 Agonistsmentioning
confidence: 99%